TEN EPIQ STEPS TO IMPROVING CARE AND OUTCOMES IN RURAL TANZANIA. (18th May 2018) - Ali, Ismat; Mwaikasu, Lusako; McMillan, Doug; Aziz, Khalid; Brenner, Jennifer; Matovelo, Dismas; Singhal, Nalini
Abstract: BACKGROUND: Maternal and child health (MCH) remains a priority globally and in Mwanza Region, Tanzania, where under-five mortality exceeds 100/1000 live births. Facility-based Quality Improvement (QI) is critical to enhancing MCH service delivery. The 'Evidence-based Practice for Improving Quality (EPIQ)' approach aims to equip clinical providers with basic QI understanding and skills. In Canada, EPIQ introduction has led to significant newborn intensive care improvements. OBJECTIVES: To adapt, pilot and evaluate an EPIQ workshop for rural Tanzania. DESIGN/METHODS: The 10-step EPIQ process is introduced through a practical, clinically-focused, hands-on workshop. A team of Canadian EPIQ experts with African partnership experience initially adjusted the EPIQ package for a Tanzanian pilot. They then facilitated a one day EPIQ training-of-trainers to QI-interested Tanzanian university faculty and health managers. The new facilitators then delivered the training to selected local health providers. The EPIQ training was evaluated through facilitator and provider (1) pre/post QI-focused knowledge tests, (2) pre/post QI confidence surveys and (3) post-workshop satisfaction surveys. Post training semi-structured group interviews also collected feedback on workshop content and format from facilitators. Written surveys and tests were analyzed using descriptive statistics and aggregate scores; semi-structured interview notes were reviewed for key themes, recommendations and representative quotations. RESULTS: Workshop content including flipcharts, workbooks and locally-relevant cases were prepared. In September 2017, workshops were delivered to 16 facilitators and 29 providers in Mwanza. Post-workshop, overall knowledge scores increased by +7.6% (facilitators) and +2.1% (providers). Aggregate confidence survey scores (5-point Likert) increased for both groups by a median increase of 1 (20%). Participant workshop satisfaction scores averaged 4.7/5. Interviews suggested indicated content was perceived as very relevant however too heavy for allocated time; certain wording was too complex for the language setting. Participants reported that the small group and hands-on format encouraged skill development and EPIQ tools equipped for critical thinking and problem solving. It was strongly recommended to increase workshop length to two days. CONCLUSION: A clinically-focused, participatory EPIQ training was feasible and well-received in this setting. Despite self-reported confidence increase, a lacking associated knowledge increase may reflect content too complex, limited workshop duration or poor knowledge test face validity. Future considerations should include revised content and/or knowledge testing tool, extended length, and post-workshop implementation follow-up.